Atheist overreach: what atheism can't deliver - Smith, Christian (Oxford University Press, 2019)
"In recent years atheism has become ever more visible, acceptable, and influential. Atheist apologists have become increasingly vociferous and confident in their claims. In Atheist Overreach, Christian Smith takes a look at the evidence and explains why we ought to be skeptical of these atheists' claims about morality, science, and human nature"--